Reviews. (1st May 2018) - Drábek, Pavel; Raw, Laurence
Adapting Translation for the Stage, Geraldine Brodie and Emma Cole (eds) (2017) London and New York: Routledge. 298 pp., ISBN: 9781138218871, h/bk, £110.00; ISBN: 9781315436814, e/bk, £35.99The Translator on Stage, Geraldine Brodie (2018) New York: Bloomsbury. 208 pp., ISBN: 9781501322112, h/bk, £96.00; ISBN: 9781501322105, p/bk, £23.99; ISBN: 9781501322136, e/bk, £25.99Writing for Radio, Christopher William Hill (2015) London: Bloomsbury, 163 pp., ISBN: 978-1-408-13983-7, p/bk, £16.99